Political Communication Cultures in Western Europe Attitudes of Political Actors and Journalists in Nine Countries - Pfetsch, B.; Pfetsch, B. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
This book offers new and compelling insight into the orientations that shape the cultures of political communication in nine Western democracies. It is a truly comparative account of the views of 2500 political elites and media elites between Helsinki and Madrid on their relationship and their exchanges.